2021
DOI: 10.24875/rmn.21000024
|View full text |Cite
|
Sign up to set email alerts
|

Very-early Guillain-Barré syndrome: Clinical characteristics, electrophysiological findings, and short-term functional outcome

Abstract: Background: Guillain-Barré syndrome (GBS) patients who present very early (< 4 days) to health-care services generally have severe clinical forms due to rapid progression. Little information exists on the clinical and short-term functional prognosis in patients with very-early GBS (VEGBS). Methods: A prospective cohort study was conducted. We performed Kaplan-Meier survival analysis to observe the recovery of independent gait between groups, where a log-rank value < 0.05 was considered significant. All statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…There have been case reports of patients presenting with encephalopathy secondary to hyponatremia who, at the time of review, found GBS or the onset of SIADH symptoms with subsequent development of GBS 17,18 . Our previously published data involving patients with very early GBS (< 4 days of evolution) found a higher prevalence of hyponatremia (37%) without a higher prevalence of dysautonomia, being approximately double what was found in the current study and persisting when compared with other international cohorts 19 .…”
Section: Discussionsupporting
confidence: 57%
“…There have been case reports of patients presenting with encephalopathy secondary to hyponatremia who, at the time of review, found GBS or the onset of SIADH symptoms with subsequent development of GBS 17,18 . Our previously published data involving patients with very early GBS (< 4 days of evolution) found a higher prevalence of hyponatremia (37%) without a higher prevalence of dysautonomia, being approximately double what was found in the current study and persisting when compared with other international cohorts 19 .…”
Section: Discussionsupporting
confidence: 57%